Continuous blood oxygen saturation detection with single-wavelength photoacoustics - Peng, Qiwen (2015)
Blood oxygen saturation (SO2) reflects the oxygenation level in blood transport and tissue. Previous studies have shown the capability of non-invasive quantitative measurements of SO2 by multi-wavelength photoacoustic (PA) spectroscopy for diagnosis of brain, tumor hemodynamics and other pathophysiological phenomena. However, those multi-wavelength methods require a tunable laser or multiple lasers which are relatively expensive and bulky for filed measurement environment and applications. Besides, the operation of multiple wavelengths, calibration procedures and data processing gets system complicated, which reduces the feasibility and flexibility for continuous real-time monitoring. Here we report a newly proposed method by combining PA and scattered light signals wherein imposing a hypothesis that scattering intensity is linear to the concentrations of oxygenated hemoglobin and deoxygenated hemoglobin weighed by blood scattering coefficients. A rigorous theoretical relationship between PA and scattering signals is thus established, making it possible that SO2 can be measured with only one excitation wavelength. To verify the theory basis, both dual-ink phantoms and fresh porcine blood sample have been employed in the experiments. The phantom experiment is able to quantify the concentration of mixed red-green ink that is in precise agreement with pre-set values. The ex vivo experiment with fresh porcine blood was conducted and the results of the proposed single-wavelength method achieved high accuracy of 1% - 4% errors. These demonstrated that the proposed single-wavelength SO2 detection is able to provide non-invasive, accurate measurement of blood oxygenation, and herein create potential for applying it to real clinical applications with low cost and high flexibility.